2004
DOI: 10.1111/j.1464-5491.2004.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin treatment on the body composition of Type 2 diabetic patients

Abstract: Over 6 months, insulin therapy leads to a weight gain of 1.7 kg because of an increase in both fat and fat-free mass. When body composition is determined by bioelectrical impedance analysis, the results are biased by fluctuations in hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…Weight was measured before breakfast, in undergarments, on plethysmographic weighing scales, calibrated prior to each test to the nearest 0.01 kg. Percentage of fat and fat-free mass was determined using a three-compartment model as described previously [32]. Measurements of body volume were performed by air displacement plethysmography, and total body water was estimated using bioelectrical impedance.…”
Section: Body Compositionmentioning
confidence: 99%
“…Weight was measured before breakfast, in undergarments, on plethysmographic weighing scales, calibrated prior to each test to the nearest 0.01 kg. Percentage of fat and fat-free mass was determined using a three-compartment model as described previously [32]. Measurements of body volume were performed by air displacement plethysmography, and total body water was estimated using bioelectrical impedance.…”
Section: Body Compositionmentioning
confidence: 99%
“…6,[87][88][89] Weight gain in type 2 patients occurs through increases in both fat and fat-free mass. 88,89 In the DCCT, even modest weight increases had a negative impact on lipid profiles and systolic blood pressure. 90 Similar findings in type 2 patients were noted in a report from the Swedish National Diabetes Register.…”
Section: Weight Gainmentioning
confidence: 99%
“…Body composition was affected by the fl uctuations of body hydration. 14 The bone mass was higher in diabetics than in controls: it had low statistical signifi cance in the age group of 61-80 years while in the other age group it was high but failed to reach statistical signifi cance. Strotmeyer et al 15 also reported higher bone mass in diabetic patients compared with that of non-diabetics.…”
Section: Discussionmentioning
confidence: 88%